Does economic freedom affect entrepreneurship? Insights from Africa - Folorunsho M Ajide (Universitas Islam Indonesia, 2021)
Purpose - Literature suggests that entrepreneurship can serve as a veritable tool for providing decent employment and improving economic prosperity. Therefore, the objective of this study is to examine the impact of economic freedom on entrepreneurship in Africa.Design/methodology/approach - The study employs data of 18 African countries covering a period of 2007-2018. The analysis is based on the following techniques: Panel-Corrected Standard Errors (PCSE), generalized method of moments, Hausman–Taylor IV estimator and Driscoll-Kraay standard errors.Findings - Finding based on Panel-Corrected Standard Errors (PCSE) technique reveals that economic freedom and its dimensions improve the level of entrepreneurship in Africa. This finding is robust to other alternative estimation techniques. Secured property right, relaxed tax burden, monetary freedom, trade freedom, freedom from corruption, investment freedom, financial freedom, business freedom and labor freedom have positive impact on African entrepreneurship.Practical implications - The study, hence, suggests that policy should be implemented to maximize the level of economic and fundamental freedom of citizens to encourage indigenous entrepreneurs in Africa. Quality of infrastructure should be improved as well as simplification of firms’ registration procedures. African government also needs to build effective and efficient institutional framework to maintain government integrity in Africa.Originality/value - The position of African countries in the nexus between economic freedom and entrepreneurship is rarely discussed in the literature. Hence, this study contributes in this respect and showcases how economic freedom influence the decision to engage in entrepreneurial venture in African perspectives